A Pressure- and Frequency-Dependent Multiscale Model for Describing the Wave Propagation Characteristics of Fluid-Saturated Porous Media - Jingyang Yang; Fanchang Zhang; Jun Wu (Lithosphere)
The mechanism of wave propagation in fluid-saturated porous media is influenced by pressure and frequency. Pressure dependence is mainly dominated by the opening and closing of compliant and stiff pores in rocks, as well as nonlinear deformation respect to high-order elastic constants. Frequency dependence is mainly reflected in the dispersion and attenuation caused by wave-induced fluid flow (WIFF). Therefore, the propagation characteristics of seismic waves in subsurface rocks when pressure and frequency are coupled have broad practical significance, such as geofluid discrimination and in situ stress detection. A new equivalent elastic modulus applicable to fluid-saturated porous media has been established, which simultaneously considers the effects of pressure and WIFF. First, the dual-porosity model is incorporated to account for the changes in rock porosity under pressure and corresponding linear and nonlinear deformations. Then, based on the heterogeneity of rock at the mesocale and microscale, a unified pressure- and frequency-dependent elastic modulus over a wide frequency band is established using the Zener model. The wave equation of fluid-saturated porous media is constructed using the new model, and the pressure- and frequency-dependent phase velocities are derived. Rock physics and digital simulation experiments are applied to analyze the variation of elastic parameters and velocity with pressure and frequency. Comparison with experimental measurement data shows that the new model has higher accuracy than traditional models, especially in the low effective pressure region and the frequency band respect to seismic exploration.